Work effectiveness of civil servants and contract employees of the population and civil registration office, Kutai Timur District: Efektivitas kerja pegawai negeri sipil (pns) dan pegawai tenaga kerja kontrak daerah (tk2d) di dinas kependudukan dan pencatatan sipil Kabupaten Kutai Timur - Hediana Nur Rahmah (JOURNAL OF GOVERNMENT SCIENCE, 2020)
This comparative study describes and analyzes work effectiveness of civil servants (PNS) and contract employees (TK2D) of the Population and Civil Registration Office (DISDUKCAPIL) of Kutai Timur District. This qualitative descriptive research uses purposive sampling technique and primary as well as secondary data as data sources. The results of this study concluded that work effectiveness of contract employees outperforms those of civil servants. This is influenced by employee status, remuneration system, and workplace assignments. Salaries of those who have “vulnerable” status (contract employees) depend on such a status and attendance record. To increase or maintain their salaries, they should have a good attendance record. Furthermore, as they are mostly assigned to technical works in computer operating system, data processing and data verification for public service, this requires work discipline and performance. All of these aspects motivate them to do their best. On the other hand, permanent status (meaning fixed salaries) and the degree of discipline (which does not much influence allowances) have considerable impact on civil servants’ work motivation, hence, work effectiveness. It is common, therefore, to see civil servants come late to the office and thus their workplace discipline is questioned.   Keywords: work effectiveness, civil servants, contract employees, PNS, TK2D